Metabolic Reprograming of Mononuclear Phagocytes in Progressive Multiple Sclerosis - Tannahill, Gillian Margaret; Iraci, Nunzio; Gaude, Edoardo; Frezza, Christian; Pluchino, Stefano (Frontiers in Immunology, 2015)
Multiple sclerosis (MS) is an inflammatory and demyelinating disease of the central nervous system (CNS). Accumulation of brain damage in progressive MS is partly the result of mononuclear phagocytes (MPs) attacking myelin sheaths in the CNS. Although there is no cure yet for MS, significant advances have been made in the development of disease modifying agents. Unfortunately, most of these drugs fail to reverse established neurological deficits and can have adverse effects. Recent evidence suggests that MPs polarisation is accompanied by profound metabolic changes, whereby pro-inflammatory MPs (M1) switch toward glycolysis, whereas anti-inflammatory MPs (M2) become more oxidative. It is therefore possible that reprogramming MPs metabolism could affect their function and repress immune cell activation. This minireview describes the metabolic changes underpinning macrophages polarisation and anticipates how metabolic re-education of MPs could be used for the treatment of MS.